PELATIHAN PUBLIC SPEAKING DI KOMUNITAS STAND UP INDO BOGOR - Ridwan, Muhamad; ., Sukarelawati; Fitriah, Maria (JURNAL KOMUNIKATIO, 2020)
Talent event stand up comedy television in Indonesia to cause the number of people who want to learn this art by joining to communities to study to be a komika by following a variety of training one of them is public speaking training. The purpose of this research to see how process of training public speaking of the community Stand Up Indo Bogor. This research in a qualitative deskiptif by using two technique data collection the primary and secondary data. The results of the study showed the training process public speaking of the community Stand Up Indo Bogor reference of a high effective communication namely by train communicator, prepare the message, control the audience, see the quality of media the messenger, and get an as expected. The conclusion of this research is training public speaking in a community Stands Up Indo Bogor has been running well in accordance with the process of effective communication, but there are additional training materials needed to become a komika as the training techniques non-verbal (expression and gesture), adjusting references, exchanging experiences to analyze the audience, doing sound checks before performing, and making the audience laugh as feedback. Keywords: stand up comedy; public speaking; community; training.